PANCASILA DAN PENGUATAN KEWARGANEGARAAN SIPIL DI INDONESIA - ., Winarno (PKn Progresif, 2008)
Ideals of citizenship or civic ideal in Indonesia became one of the demands of the reform movement. One effort that can be done is the revitalization of five principle of Pancasila because he became philosophical basis, the content and purpose of citizenship education. Revitalization of five principle of Pancasila done properly functioning basic position as the state and national ideology that has implications for the three aspects of the philosophical, political and juridical. Interwoven basic values embodied in the five principle of Pancasila capable of coloring and strengthen the formation of an ideal citizenship Indonesia's future